To Study the Influence of Empty Fruit Bunch (EFB) on the Mechanical Properties of Cement Board in Panelling - Kamaruddin, Nor Asmalyana; bin Ja'afar, Azman (Progress in Engineering Application and Technology, 2022)
The use of oil palm empty fruit bunch (OPEFB) fibre in organic composites has been developed in order to displace the present material predominantly wood fibre. The performance and the potential required characteristics contributed to several investigations and research activities which revealed the ability of this material as an adequate, safe and economic material. In this study, the ratio of fibre used were 0%, 15%, 17%, 20% and 23%. This research focuses on the effect of using different ratio on mechanical strength properties of EFB fibre cement board and to determine the optimum ratio. A test sample were performed for Thickness Swelling (TS) and Water Absorption (WA), Density, Modulus of Rupture (MOR) and Modulus of Elasticity (MOE). The results of the test indicate that among all cement boards produced using the above ratios that contains fibre, none of that satisfy the BS EN 310:1993 for MOR and MOE but only 0% of fibre that satisfy the both tests. For water absorption, it also not achieves the standard. However, for thickness swelling and density obtained from the test for ratio that contains fibre achieved the standard. The study had identified that the optimum fibre ratio is 15% to produce the cement board by using empty fruit bunch (EFB).